Safety and efficacy of rituximab in systemic sclerosis (DESIRES): open-label extension of a double-blind, investigators-initiated, randomised, placebo-controlled trial. (August 2022) - Ebata, Satoshi; Yoshizaki, Ayumi; Oba, Koji; Kashiwabara, Kosuke; Ueda, Keiko; Uemura, Yukari; Watadani, Takeyuki; Fukasawa, Takemichi; Miura, Shunsuke; Yoshizaki-Ogawa, Asako; Okiyama, Naoko; Kodera, Masanari; et al.
Summary: Background: Results from the double-blind phase 2 DESIRES trial showed that rituximab improves skin thickening in systemic sclerosis. Here, we present the findings of a subsequent 24-week open-label extension phase. Methods: Patients with systemic sclerosis aged 20–79 years, who fulfilled the 2013 American College of Rheumatology and European League Against Rheumatism classification criteria, with a baseline modified Rodnan Skin Score (mRSS) of 10 or greater were enrolled into the DESIRES trial, which was an investigator-initiated, phase 2, double-blind, randomised controlled trial of rituximab versus placebo conducted at four sites in Japan. After completion of 24 weeks of treatment with either rituximab or placebo, patients in both groups received a further 24 weeks of rituximab (375 mg/m 2 intravenously, once per week for 4 consecutive weeks) in an open-label extension. The primary endpoint of the double-blind trial was mRSS at week 24, which was reassessed at week 48 in the open-label extension. All endpoints were exploratory. Safety analyses included all participants who received at least one dose of study drug; efficacy analyses included those who had received at least one dose and undergone efficacy assessment at 24 weeks in the double-blind phase and at 48 weeks in the extension phase. The DESIRES study is registered with ClinicalTrials.gov, NCT04274257, and UMIN-CTR, UMIN000030139. Findings: Between Nov 28, 2017, and Nov 6, 2018, 56 patients were randomly assigned to either rituximab (n=28) or placebo (n=28) in a double-blind study. 26 patients initially assigned to rituximab and 20 assigned to placebo transitioned to the open-label extension and all received at least one dose of rituximab; 24 participants in the rituximab–rituximab group and 19 in the placebo–rituximab group completed the extension phase. In the rituximab–rituximab group, there was an improvement in mRSS from baseline at week 24 (–5·81 [SD 3·16]), with further improvement at week 48 (–8·88 [3·10]). In the placebo–rituximab group, mRSS worsened at week 24 (2·14 [SD 5·51]) but improved at the week 48 assessment (–6·05 [4·43]). One patient each in the rituximab–rituximab and placebo–rituximab groups experienced one serious adverse event during the open-label phase (cholangitis and pneumococcal pneumonia, respectively). There were no deaths during follow-up. Interpretation: Two courses of rituximab is a safe treatment that can provide sustained improvement in systemic sclerosis for at least 48 weeks. Funding: Japan Agency for Medical Research and Development. Translation: For the Japanese translation of the abstract see Supplementary Materials section.